Mais de um sentido: Facilitando a autoria, sincronização e execução de efeitos sensoriais em linguagens multimídia - Abreu, Raphael; Bezerra, Eduardo; Santos, Joel (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
Advances in ubiquitous computing have spurred research aimed at increasing user immersion in multimedia applications. One such research is the coupling of sensory effects in multimedia presentations. That is, to enable forms of interaction with human senses other than usual sight and hearing. However, the development of applications with sensory effects needs an authoring effort to synchronize sensory effects with audiovisual content. In addition, interactive applications lack abstractions to facilitate the authoring of sensory effects. Therefore, this paper presents works on three approaches to facilitate this scenario.